Gap acceptance by pedestrians - Harrell, W. Andrew; Bereska, Tami (My University, 1992)
The riskiness of street crossing behavior of 75 individuals and groups of pedestrians was observed. Gap acceptance, or the elapsed time before a pedestrian initiated a crossing at a marked crosswalk and the time until a vehicle passed through the crosswalk, was the measure of risk. Pedestrian groups containing at least one infant tended to choose longer gaps, i.e., they were less risky in their crossing. Gap acceptance was also more conservative as the mean age of the pedestrian group increased. Gap was not affected by the sex ratio of the group or the volume of traffic passing through the intersection.
Keywords: pedestrians; risk